### 2 Answers

Relevance

- PhilipLv 62 months ago
y = a(b^x).

(0,-1)........on y ---> -1 = a(b^0) = a, ie., -1 = a(1) = a. Then a = -1

(2,-0.25)...on y ---> -0.25 = -(b^2). Then b^2 = (1/4) and b = (+/-) (1/2).

Now (-2,-4) on the graph is shown to be on y. Therefore -4=-[(-1/2)^(-2)]...(1). or

-4 = -[(1/2)^(-2)]...(2).

For (1) holding, 4 = -(1/2)^(-2) = -[2^(-1)]^(-2)] = -2^[(-1)(-2)] = -2^(2) = -4 which is not

true. Therefore b =/= -(1/2).

For (2) holding, 4 = (1/2)^(-2) = [2^(-1)]^(-2) = 2^[(-1)(-2)] = 2^(2) = 4 which is true.

Therefore b = (1/2).

- Login to reply the answers

- coreyALv 62 months ago
You have y = a*b^x and you also know that (0,-1) and (2,-.25) are also on the curve.

Start with (0,-1)

-1 = a*b^0

-1 = a*1

a = -1

y = (-1)b^x, use (2,-.25) to find b:

-.25 = (-1)*b^2

b^2 = .25

b = .5

- Bob2 months agoReport
Thank you very much

- Login to reply the answers

Still have questions? Get your answers by asking now.